Design and validation of a diagnostic test for first-year students of the Mathematics Teaching program at UNED (Revista Electrónica Calidad en la Educación Superior, 2025)
The objective of this article is to describe the process of developing and validating a diagnostic test in Mathematics, which will contribute to identifying strengths and weaknesses in prior knowledge required to achieve new learning, additionally, it will provide information for educators to recommend the use of reinforcement modules and adjust or develop new teaching strategies. The theoretical references are based on a series of recommendations for creating multiple-choice items and on Hurtado (2021) for determining the quantity and classification of test items. Regarding the methodology, it follows a qualitative approach. As a result of this design process, various adjustments were made to the proposed items, so that they evaluate the desired objective and obtain the required level of difficulty.
Keywords: secondary education; mathematics; formative evaluation; multiple response test; content leveling; diagnostic test